Sonographic characteristics of pharyngoesophageal diverticula: Report of 14 cases and review of the literature. Issue 6 (16th December 2015) - Wang, Yang; Song, Yangguang
ABSTRACT: Purpose: Our aim was to report the characteristics of pharyngoesophageal diverticula on sonographic (US) examination. Methods: We retrospectively reviewed the medical records and images of 14 patients whose pharyngoesophageal diverticula had been found first on thyroid US. The diagnoses had been confirmed on barium‐swallow esophagography. Results: All nodules were located posterior to the left thyroid lobe, having a clear hypoechoic border with the thyroid. The maximal diameter ranged from 0.7 to 3.3 cm (mean, 1.3 cm). The appearances on US examination were variable according to the size and amount of air inside the sac. Three nodules less than 1 cm contained little air and were hypoechoic, with internal microbubbles mimicking microcalcifications. Four nodules of larger size contained little air and had inhomogeneous echogenicity with internal echogenic spots and lines without posterior shadowing. Seven nodules contained more air, and an arc‐shaped hyperechoic line with a posterior reverberation artifact was observed within the sac. After the patients swallowed water, the shape and echogenicity of the nodules had changed, and on US, all nodules were seen to connect with the adjacent esophagus. Subsequent barium‐swallow esophagography confirmed the diagnoses. Conclusions: An air‐containing nodule located posterior to the left thyroid and connected to the cervical esophagus is indicative of a pharyngoesophageal diverticulum on US examination. Swallowing maneuvers are helpful in differentiating these diverticula from thyroid and parathyroid nodules. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound 44 :333–338, 2016